Karakteristik Organoleptik dan Kadar Kalium Cookies Lidah Kucing Substitusi Tepung Kacang Merah dan Tepung Pisang Kepok untuk Penderita Hipertensi - Kharisma, Dhea Silvia; Srimiati, Mia (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2023)
This study aimed to analyze the effect of substituting of cat's tongue cookie in the formulations of red bean flour (Phaseolus vulgaris L.) and banana flour (Musa Paradisiaca Linn) on organoleptic characteristics and potassium levels. The design of this study was experimental using a completely randomized design (CRD) consisting of 7 treatments. Organoleptic test results data were analyzed using the Kruskal Wallis test, if significant, continued with the Mann-Whitney further test. While the results of proximate levels, potassium levels and sodium levels were analyzed using an independent t-test. The results of the overall Kruskal Wallis test analysis showed that there were significant differences in each treatment (p<0.05). The results of the organoleptic analysis of the hedonic test showed that the selected formula cat tongue cookie was F3.2 (20:50:30). The proximate analysis results of the selected cat tongue cookies contain water content of 3.95%, ash content of 1.74%, energy 535.42%, fat 31.64%, protein 9.54%, carbohydrates 53.12%, potassium 475.84 mg/100g and sodium 192.11 mg/100g. The potassium contribution of selected cat tongue cookies was 475.84 mg/100g and 247 mg per serving (52 grams). The conclusion of this study was that the levels of potassium and sodium levels had significant differences (p<0.05) in each analysis. Sugesstion for this research need to analyze the biovailability of potassium, long shelf life and fiber content of cat's tongue cookies with the substitution of red bean flour and kepok banana flour. Keywords – Kepok Banana Flour, Kidney Bean Flour, Lidah Kucing Cookies, Potassium.